PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KULIAH KERJA NYATA DI DUSUN GAMELAN, DESA SENDANGTIRTO, KAPANEWON BERBAH, SLEMAN - Cahyono, Sadin; Ikhlas Yulianto, Muhammad; Putri Aprilia, Adinda; Kurniawan Putra, Muhammad Rafi; Munthe, Ryan Giggs; Astuti, Febriani (DHARMA BAKTI, 2024)
Community empowerment is important to improve the quality of life and active community participation in local regional development. One way can be implemented is through the Community Service Program (KKN). This program is implemented in Gamelan Hamlet, Sendangtirto Village, Kapanewon Berbah, Sleman, which has large natural and human resources and can be improved. The research method used involves active community participation and observation of needs in the community. Furthermore, the programs provided include live pharmacy and the formation of study groups. The research results show that the KKN Program is able to make a significant contribution to empowering the Gamelan Hamlet community. Through collaboration between students, lecturers and the local community, this program has succeeded in providing skills training, increasing awareness of local potential and building strong social networks. In this process, it was identified that there was an increase in active community participation in decision-making for managing the living environment through the living pharmacy program and an increase in children's interest in learning through study groups.